Bi-\( Γ \)-Hyperideals and Green’s Relations in Ordered \( Γ \)-Semihypergroups - Omidi, Saber; Davvaz, Bijan (Eurasian Mathematical Journal, 2017)
In this paper, we proceed with the study of the basic properties of bi-\( Γ \)-hyperideals of ordered \( Γ \)-semihypergroups. The purpose of the present paper is to study the Green’s relations on ordered \( Γ \)-semihypergroups.